Can response to locoregional therapy help predict longterm survival after liver transplantation for hepatocellular carcinoma? A systematic review. Issue 3 (March 2017) - Morris, Paul D.; Laurence, Jerome M.; Yeo, David; Crawford, Michael; Strasser, Simone I.; McCaughan, Geoffrey W.; Sandroussi, Charbel
Abstract : For a selected group of patients with hepatocellular carcinoma (HCC), liver transplantation (LT) represents the best chance of a cure. Organ shortages necessitate an efficient allocation of resources and careful prioritization on the transplantation waiting list. In this review, we aim to collate and evaluate the published evidence for using response to locoregional therapies (LRTs), measured by modified Response Evaluation Criteria in Solid Tumors (mRECIST), as a predictor of longterm survival after LT. Our aim was to assess whether response to LRTs before LT for HCC, as measured by the Response Evaluation Criteria in Solid Tumors (RECIST) or mRECIST criteria, can help predict recurrence‐free and/or longterm survival outcomes. We searched MEDLINE, Embase, and the Cochrane database. We included randomized controlled trials (RCTs), cohort, case control, and case series studies. Poster and conference abstracts were included. Studies were required to use RECIST or mRECIST criteria when assessing tumor response and were limited to LT for HCC only. A total of 15 records were included in the final systematic review: 7 published manuscripts and 8 conference abstracts. No RCTs were identified. Several included articles were conference abstracts with limited data available. No RCTs were found, and no meta‐analysis was undertaken. Several retrospective cohort studies were identified that demonstrated statistically significant differences in survival and recurrence between different RECIST criteria after LT. Liver Transplantation 23 375–385 2017 AASLD .